Elevated cyclic AMP levels in T lymphocytes transformed by human T-cell lymphotropic virus type 1 - Kreß, Andrea; Schneider, Grit; Pichler, Klemens; Kalmer, Martina; Fleckenstein, Bernhard; Grassmann, Ralph (Journal of Virology, 2010)
Human T-cell lymphotropic virus type 1 (HTLV-1), the cause of adult T-cell leukemia/lymphoma (ATLL), transforms CD4+ T cells to permanent growth through its transactivator Tax. HTLV-1-transformed cells share phenotypic properties with memory and regulatory T cells (T-reg). Murine T-reg-mediated suppression employs elevated cyclic AMP (cAMP) levels as a key regulator. This led us to determine cAMP levels in HTLV-1-transformed cells. We found elevated cAMP concentrations as a consistent feature of all HTLV-1-transformed cell lines, including in vitro-HTLV-1-transformed, Tax-transformed, and patient-derived cells. In transformed cells with conditional Tax expression, high cAMP levels coincided with the presence of Tax but were lost without it. However, transient ectopic expression of Tax alone was not sufficient to induce cAMP. We found specific downregulation of the cAMP-degrading phosphodiesterase 3B (PDE3B) in HTLV-1-transformed cells, which was independent of Tax in transient expression experiments. This is in line with the notion that PDE3B transcripts and cAMP levels are inversely correlated. Overexpression of PDE3B led to a decrease of cAMP in HTLV-1-transformed cells. Decreased expression of PDE3B was associated with inhibitory histone modifications at the PDE3B promoter and the PDE3B locus. In summary, Tax transformation and its continuous expression contribute to elevated cAMP levels, which may be regulated through PDE3B suppression. This shows that HTLV-1-transformed cells assume biological features of long-lived T-cell populations that potentially contribute to viral persistence. Copyright © 2010, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up